Gabon : Third Review under the Extended Arrangement Under the Extended Fund Facility, and Requests for Waiver of Nonobservance of Performance Criterion, and Modifications of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2019)
Political risks appear to have subsided with the completion of legislative and local elections in October. The economy is slowly recovering, fiscal consolidation has continued, inflation has remained low, and the trade balance has improved. The recovery is expected to firm up in 2019 and the medium-term outlook is still promising, although risks remain mostly tilted to the downside.